Methods for detection-recognition of radar, acoustic, optical and infrared signals of unmanned aerial vehicles - Kartashov, V.M.; Pososhenko, V.A.; Voronin, V.V.; Kolesnik, V.I.; Kapusta, A.I.; Rybnikov, N.V.; Pershin , E.V. (Radiotekhnika, 2021)
The protection of various objects against the impact of unmanned aerial vehicles (UAVs), which carry a potential threat in the military, economic and everyday areas of human activity, is one of the urgent tasks of our time. Currently, there are a large number of publications devoted to the description of methods and systems based on different physical principles designed to detect and observe UAVs against the background of existing interference. They consider the reception channels, methods of processing the received information signals and their subsequent intelligent analysis. It is shown, that the known methods of energy detection of UAV signals are insufficiently effective, since the operation is performed, as a rule, against a background of noise that has certain structural similarities with the UAV signal. Considerable attention is paid to the methods for interpreting the obtained data using trained neural networks. Since the number of publications in this area is constantly increasing, the task of analyzing, generalizing and systematizing the data available in the literature is relevant in accordance with this. The article is an overview and it is devoted to the generalization and systematization of known methods of receiving and processing radar, acoustic, optical and infrared signals for detection-recognition, measurement of coordinates and parameters of UAV movement.